Engineering of Poly Lactic Acids (PLAs) for melt processing: Material structure and thermal properties. Issue 8 (6th October 2016) - Barletta, M.; Moretti, P.; Pizzi, E.; Puopolo, M.; Tagliaferri, V.; Vesco, S.
ABSTRACT: Bottles and other packaging account for approximately 70% of the global market of biopolymers, which include both biodegradable and durable materials. Durable materials account for the vast majority of the market, especially the bottles. Degradable polymers are instead refrained by the often‐insufficient mechanical and thermal properties, which limit their usage to single‐use packaging items at ambient temperature and in dry conditions. In this respect, the present work deals with the development and manufacturing of innovative and custom‐built Poly Lactic Acids (PLAs) for injection and compression molding, which are designed to be compostable, suitable for food contact and characterized by a good compromise of mechanical properties and thermal stability. A commercial grade PLA was, therefore, compounded in a twin‐screw co‐rotating extruder by the addition of maleated and glycidyl methacrylate PLAs as chain extenders and micro‐lamellar talc as mineral filler and nucleation promoter. Compatibilization between PLA, chain extenders and mineral filler was, therefore, investigated. Differential Scanning Calorimetry (DSC) and Fourier Transform Infrared Spectroscopy (FTIR) were performed to evaluate the material structure and thermal response of the pellets after reactive compounding extrusion. The experimental findings show that material structure and, especially, crystallization of the PLA can be controlled by fine‐tuning the compound formulation as well as by setting of the operational parameters. In addition, achievement of the appropriate crystallization degree in the polymer is found to lead to composite materials, which can boast very good thermal stability. Accordingly, the custom‐built PLA formulations feature the potential to expand significantly the fields of application of non‐durable polymers, thus posing a valid alternative to both durable biopolymers and conventional plastics in injection and compression molding process. © 2016 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2017, 134, 44504. Abstract :